The potential of the zooplankton resting-stage bank to restore communities in permanent and temporary waterbodies. (12th July 2018) - Eskinazi-Sant'Anna, Eneida Maria; Pace, Michael L
Abstract: We assessed how the viability and diversity of the zooplankton resting-stage bank can be affected by predictable and unpredictable hydroperiods using permanent and temporary lakes. We hypothesized that the zooplankton resting-stage bank in temporary waterbodies would be affected by the length of the dry period (seasonal, intermittent and episodic). We also tested the role of dried macrophyte mats in preserving resting-stage banks in temporary lakes. Laboratory experiments were conducted with sediment samples from two permanent waterbodies and three temporary shallow lakes that undergo dry periods of different lengths (seasonal, intermittent and >10 years dry). The results of the experiments suggested that the dry period length significantly affected the viability and diversity of the resting-stage bank, affecting its potential role in zooplankton community recovery. Longer dry periods also affected the temporal hatching response of resting stages from temporary lakes: species from unpredictably drying waterbodies experienced delayed hatching. Resting-stage viability and richness were largely and positively influenced by dried macrophyte mats, which surpassed the efficiency of the sediment as a substrate for conserving resting stages. Our results provide new insight on the functional role of macrophytes indicating that these beds are pivotal in conserving resting stages and increasing zooplankton community resilience.